Silencing hepatic MCJ attenuates non-alcoholic fatty liver disease (NAFLD) by increasing mitochondrial fatty acid oxidation - Lucía Barbier-Torres (Nature Portfolio, 2020)
Non-alcoholic fatty liver (NAFLD) disease causes degeneration of the liver, affects about 25% of people globally, and has no approved treatment. Here, the authors show that the therapeutic siRNA-driven silencing of MCJ in the liver is an effective and safe treatment for NAFLD in multiple mouse models.